A molecular phylogenetic study on South Korean Tettigonia species (Orthoptera: Tettigoniidae) using five genetic loci: The possibility of multiple allopatric speciation - Kim, Tae-Kyu; Han, Taeman; Kim, Tae-Woo; Park, In Gyun; Kim, Seonghyun; Park, Haechul (Zootaxa, 2016)
In Korea, members of the genus Tettigonia have been known as two species, T. ussuriana and T. dolichoptera dolichoptera. However, the taxonomic status of the Jeju Island population of T. ussuriana (JJ-TU) is in question, relative to the mainland population (ML-TU), because of their different body sizes and ratios of wing length. To clarify the relatedness of JJ-TU and ML-TU, we examined the genetic variation and phylogenetic relationships within and between T. ussuriana and related species collected in South Korea, using five genetic loci: three mitochondrial genes (cytochrome c oxidase subunit 1 [CO1], cytochrome c oxidase subunit 2 [CO2], NADH dehydrogenase 1 [ND1]) and two nuclear loci (second internal transcribed spacer [ITS2], and tubulin alpha-1 [TA1]). Unexpectedly, the JJ-TU population is explicitly sister to T. d. dolichoptera, with low genetic distance (0.76–1.22% in CO1), indicating no direct connection with the ML-TU population; this finding suggests a recent divergence involving rapid morphological change without gene flow between JJ-TU and mainland T. d. dolichoptera. The separation of these populations from their common ancestor was caused by geographical isolation during last glacial age. This finding indicates that the JJ-TU population should be elevated to the rank of subspecies, at the very least. Furthermore, the ML-TU population was also revealed to have four genetically divided groups (group A–D) from four localized populations, but no significant morphological differences exist among them. The genetic difference (range 3.19–4.10% in CO1) between group A + B and C + D was especially large, suggesting that cryptic speciation has widely occurred within the mainland areas, caused by allopatric isolations resulting from mountain barriers.